Representation of An American Family Consumption Pattern: The Simpsons in Leisure Time - Heshmat Sadat Moinifar; Najmeh Mohammadkhani (Taḥqīqāt-i Farhangī-i Īrān)
Everyday life representation is the subject of many media productions in the United States. While talking about everyday life, family could be very significant factor. Many different television genres in US such as soap operas and sitcoms which their emergence dated back to 1950s, have specified their topics to representation of family relations, dilemmas and problems. Leisure time and consumption patterns in a consumer society could be important in a sense that family relation, the way of choosing those patterns and their representation, could clarify the form and types of family relations in United States. Generally, understanding a family could be taken as a small piece of the greater society. The subject of study in this article is The Simpsons situation comedy. This famous situation comedies’ reputation has surpassed many cultural borders dates back to 1980s. As this sitcom is about American everyday life has absorbed many American and non-American viewers. This article will study the seasons 3-8 of this sitcom to answer the two following questions: 1. How every member of the Simpsons family, personally spend their leisure time? 2. How the Simpsons family spend their leisure time collectively? The theoretical base of this article is Stuart Hall`s theory of representation and the method is semiology. The unit of analysis in related sections is sequence and scene and in non-related sections is the subject of the special section.